Data from: Prednisolone induces osteoporosis-like phenotypes via focal adhesion signaling pathway in zebrafish larvae - Lei, Huo; Wang, Lei; Yang, Zhaoyao; Li, Pingyuan; Geng, Dechun; Xu, Yaozeng (Dryad, 2018)
Patients taking glucocorticoid or glucocorticoid-like drugs for an
extended period of time may develop osteoporosis, termed
glucocorticoid-induced osteoporosis (GIOP). GIOP is the most common form
of secondary osteoporosis, but the mechanism underlying its development is
unclear. In the present study, we used prednisolone to treat zebrafish
larvae to investigate GIOP. Our RNA deep-sequencing (RNA-seq) results show
that prednisolone affects genes known to act in the extracellular region.
Therefore the extracellular region, extracellular matrix, and collagen
trimer might be involved in glucocorticoid-induced osteoporosis. Kyoto
Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that
the focal adhesion signaling pathway is the most enriched signaling
pathway in terms of differentially expressed genes (DEGs). In this
pathway, integrin subunit alpha 10 (itga10) and integrin subunit beta like
1 (itgbl1), genes encoding two adapter proteins, were down-regulated in
the prednisolone-treated larvae. Further experiments showed that
prednisolone contributes to GIOP by down-regulating itga10 and itgbl1.
gene expression dataThis file contains data of gene expression data from
qRT-PCR. This file was made with Microsoft excel 2010.Supplementary excel
1This file contains all the difference expression genes from RNA-seq
analysis. This file was made with excel 2010Supplementary excel 2This file
contains GO results which enriched by DEGs of RNA-seq. This file was made
with Microsoft excel 2010Supplementary excel 3This file contains KEGG
pathway results which enriched by DEGs of RNA-seq. This file was made with
Microsoft excel 2010
Keywords: GIOP; itgbl1; Focal adhesion signaling pathway; itga10